Common Property Resources and Hunting Territories - Berkes, Fikret (Anthropologica, 2022)
Territoriality is related to the intensity of use of an area and its resources, and territories are possible only when the benefit of holding a territory exceeds the cost of defending it. Thus an explanatory model of hunting territories needs to be dynamic to accommodate changes in the intensity of resource use and commonproperty institutions such as those governing territoriality. According to the model proposed in this paper, resource use patterns shift from community-based control to family-based control with intensification (as in the commercialization of the beaver harvest). However, if community- or family-based control breaks down (as in the case of intrusion from outside the area), open access conditions may be created, with resultant depletion of the resource. Common property institutions may be restored with the reaffirmation of local control of the resource.